Author Response: Accuracy of CT Perfusion–Based Core Estimation of Follow-up Infarction: Effects of Time Since Last Known Well. (4th October 2022) - Sarraj, Amrou; Campbell, Bruce C.V.; Pujara, Deep; Albers, Gregory W.
Abstract : We appreciate the response to our article. 1 Our study cohort was derived from consecutively enrolled patients at 9 high-volume EVT centers and did not exclude patients based on ischemic core estimates. The cohort reflects contemporary clinical practice with 25 patients with ischemic core ≥30 mL, 15 patients with ischemic core ≥50 mL, and 6 with ischemic core ≥70 mL. Rates of overestimation did not vary with core size (5/25, 3/15, and 1/6 with significant overestimation). Furthermore, only 1 patient in the cohort had an ischemic core estimate ≥70 mL and a final infarct volume of <70 mL. The findings are in line with previous studies that demonstrated 5%–7% patients have an ischemic core ≥70 mL, and <3% demonstrate overestimation that would render them ineligible for the EVT. 2, 3 Our analysis suggested that CT perfusion estimates correlate significantly with subsequent infarct volume, significant overestimation that affects potential EVT eligibility is infrequent, and the use of time-dependent ischemic core thresholds can alleviate the issue of potential undertreatment of these patients. In the light of CT ASPECTS issues with interrater reliability that may result in significant misclassification, even after training and underestimating the extent of ischemic injury in patients presenting very early after stroke ictus, 4 perfusion imaging provides more reliable estimates of early ischemic injury. Clinical trials of thrombectomy efficacy and safety in patients with large core are ongoing. The SELECT2 study obtains both noncontrast CT (NCCT) and CT perfusion imaging and therefore will help establish if there is a ceiling to thrombectomy benefit in patients with large vessel occlusion based on NCCT or perfusion imaging findings. 5